Pengaruh CSR Disclosure, Firm Size, dan Leverage Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Moderasi Perusahaan Pertambangan di BEI - Yulia Firda; Adi Rizfal Efriadi (ITB Ahmad Dahlan Jakarta, 2020)
The purpose of this study was to determine the effect of CSR disclosure, company size and leverage on firm value with profitability as a moderating variable. This research is a quantitative research. This study uses purposive sampling. The sample in this study consisted of 6 mining companies with an observation period of 5 years in a row from 2014 to 2018 so that the total sample was 30. Data analysis of this study used SPSS 19 with the classic assumption test, multiple regression analysis, t test, F test and moderation regression analysis. The results of this study indicate that CSR disclosure has no significant effect on firm value. Meanwhile, company size and leverage have a significant positive effect on firm value. Profitability as moderation weakens the relationship between CSR disclosure and leverage with firm value, however profitability as moderation is able to strengthen the relationship of company size to firm value.